Expression and Clinical Correlation Analysis Between Repulsive Guidance Molecule a and Neuromyelitis Optica Spectrum Disorders - Tang, Jinhua; Zeng, Xiaopeng; Yang, Jun; Zhang, Lei; Li, Hang; Chen, Rui; Tang, Shi; Luo, Yetao; Qin, Xinyue; Feng, Jinzhou (Frontiers in Immunology, 2022)
Objectives This study sought to explore the expression patterns of repulsive guidance molecules a (RGMa) in neuromyelitis optica spectrum disorders (NMOSD) and to explore the correlation between RGMa and the clinical features of NMOSD. Methods A total of 83 NMOSD patients and 22 age-matched healthy controls (HCs) were enrolled in the study from October 2017 to November 2021. Clinical parameters, including Expanded Disability Status Scale (EDSS) score, degree of MRI enhancement, and AQP4 titer were collected. The expression of serum RGMa was measured by enzyme-linked immunosorbent assay (ELISA) and compared across the four patient groups. The correlation between serum RGMa levels and different clinical parameters was also assessed. Results The average serum expression of RGMa in the NMOSD group was significantly higher than that in the HC group (p < 0.001). Among the patient groups, the acute phase group exhibited significantly higher serum RGMa levels than did the remission group (p < 0.001). A multivariate analysis revealed a significant positive correlation between RGMa expression and EDSS score at admission, degree of MRI enhancement, and segmental length of spinal cord lesions. There was a significant negative correlation between the expression of RGMa in NMOSD and the time from attack to sampling or delta EDSS. Conclusions The current study suggests that RGMa may be considered a potential biomarker predicting the severity, disability, and clinical features of NMOSD.